2021
DOI: 10.1021/acs.est.0c08014
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Mechanisms of Recoverable Magnetic Nanoparticles on Mitigating Golden Mussel Biofouling

Abstract: Mussel biofouling has become a problem in aquatic ecosystems, causing significant ecological impact and huge economic loss globally. Although several strategies have been proposed and tested, efficient and environment-friendly antifouling methods are still scarce. Here, we investigated the effects of recoverable magnetic ferroferric oxide nanoparticles (Fe3O4-NPs) with different sizes (10 and 100 nm), coatings (polyethylene glycol and polylysine), and concentrations (0.01 and 0.1 mg/L) on byssus adhesion-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Girardello et al (2021) found that ZnO nanoparticles alter the redox metabolism of L. fortunei. Moreover, another recent study investigated the effects of recoverable magnetic ferroferric oxide nanoparticles on byssus adhesion mediated biofouling golden mussel L. fortunei (Li et al 2021). The results confirmed the effectiveness and underlying mechanisms of magnetic ferroferric oxide nanoparticles on mitigating L. fortunei biofouling, which provides a reference for developing efficient and environmental-friendly antifouling strategies against fouling mussels.…”
Section: Oxidizing Chemicalssupporting
confidence: 55%
See 1 more Smart Citation
“…Girardello et al (2021) found that ZnO nanoparticles alter the redox metabolism of L. fortunei. Moreover, another recent study investigated the effects of recoverable magnetic ferroferric oxide nanoparticles on byssus adhesion mediated biofouling golden mussel L. fortunei (Li et al 2021). The results confirmed the effectiveness and underlying mechanisms of magnetic ferroferric oxide nanoparticles on mitigating L. fortunei biofouling, which provides a reference for developing efficient and environmental-friendly antifouling strategies against fouling mussels.…”
Section: Oxidizing Chemicalssupporting
confidence: 55%
“…Various physical and chemical measures have been performed to eliminate the negative effects caused by L. fortunei Wei et al 2016;Li et al 2019;Li et al 2021). The biofouling mussels can be temporarily dislodged through physical methods such as oxygen deprivation and thermal treatment (Perepelizin & Boltovskoy 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, adjusting the redox state of water diminished the negative impact on byssus by forestalling the cooperation between the substrate and foot proteins. Ferroferric oxide NPs alleviate the biofouling caused by L. fortunei , which is considered the most productive and highly efficient antifouling procedure against fouling mussels . Mussel-inspired chemistry in the fabrication of antibiofouling materials and the preparation strategies are shown in Figure .…”
Section: Biomimetic Design Of Antifouling Coatingsmentioning
confidence: 99%
“…Ferroferric oxide NPs alleviate the biofouling caused by L. fortunei, which is considered the most productive and highly efficient antifouling procedure against fouling mussels. 139 Mussel-inspired chemistry in the fabrication of antibiofouling materials and the preparation strategies are shown in Figure 4.…”
Section: Carbon-based Nanomaterials 311 Graphenementioning
confidence: 99%
“…The first's application to aquaculture textiles (e.g., ropes and nets) remains a challenge, 16 whereas the latter has shown good results in controlled aquatic environments. 17 Therefore, a low-cost, efficient procedure, to yield non-toxic antifoulants, is still under development.…”
Section: Introductionmentioning
confidence: 99%